INDUKSI MUTASI DAN SELEKSI IN VITRO MENGGUNAKAN ASAM FUSARAT UNTUK KETAHANAN PENYAKIT LAYU PADAPISANG AMBON HIJAU - Endang G Lestari; I Mariska; I Roostika; M Kosmiatin (Research Center for Biology-Indonesian Institute of Sciences, 2006)
Due to its high vitamin and nutrition content, banana (Musa paradisiaca L.) is deemed necessary as the mineral resources. The demand on the disease free seedlings are recently increasing. However, facing the problems of Fusarium attack in the production centers, health seedlings in the sufficient number are difficult to be provided. Hence, to solve the problems, mutative induction and in vitro selection to the shoot tip explants has been carried out in banana cv